ETNOBOTANI OBAT-OBATAN YANG DIMANFAATKAN MASYARAKAT ADAT DAYAK MERATUS DESA ULANG KABUPATEN HULU SUNGAI SELATAN KALIMANTAN SELATAN - Yalina Elsi; Trisnu Satriadi; Wiwin Tyas Istikowati (Jurnal Sylva Scienteae, 2020)
Indigenous peoples Dayak Meratus Ulang villages residing in the Meratus mountains explain that the existence of non-timber forest products is believed to be most intersect with the interests of forest communities in meeting the needs of food, boards, rituals, and others. This study aims to identify the types of non-timber forest products utilized by indigenous Dayak Meratus which is used as medicine, food, and tooling. The method used in this research is snowball. This method is done by selecting respondents based on key informant recommendations, until the data obtained saturated. The results of this study indicate that of 31 types of medicinal plants used by Ulang Village communities such as leaves, roots, bark, sap, shoots, and fruit. Treatment techniques from within and from outside.Keywords: Ethnobotan;, drugs; Dayak Meratus; medicinal plants